1967
DOI: 10.1083/jcb.33.2.281
|View full text |Cite
|
Sign up to set email alerts
|

MICRONUCLEAR RNA SYNTHESIS IN PARAMECIUM CAUDATUM

Abstract: A B S T R A C TIn a gcncration time of 8 hr in Paramecium caudatum, the bulk of D N A synthesis detected by thymidine-3H incorporation takes place in the latter part of the cell cycle. The micronuclear cycle includes a G1 of 3 hr followed by an S period of 3 -3~ hr. G2 and division occupies the remaining period of the cycle. Macronuclear R N A synthesis detected by 5'-uridine-3H incorporation is continuous throughout the cell cycle. Micronuclear R N A synthesis is restricted to the S period. Ribonuclcase remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Similar studies have been briefly reported by Alfert and Das (1959) . The results obtained here are compared with recent radioautographic studies of RNA synthesis in micronuclei of Paramecium caudatum (Rao and Prescott, 1967) and Paramecium aurelia (Pasternak, 1967) .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similar studies have been briefly reported by Alfert and Das (1959) . The results obtained here are compared with recent radioautographic studies of RNA synthesis in micronuclei of Paramecium caudatum (Rao and Prescott, 1967) and Paramecium aurelia (Pasternak, 1967) .…”
Section: Introductionmentioning
confidence: 75%
“…Studies similar to these have been performed in a related ciliate, Paramecium . Rao and Prescott (1967) labeled synchronized Paramecium caudatum with tritiated uridine for 30 min, isolated nuclei by using Triton X-100 plus spermidine (Prescott et al ., 1966), and made radioautography of the isolated nuclei . They found that micronuclei labeled with approximately one-tenth the intensity of macronuclei .…”
Section: Micronuclei Adjacent To Labeled Macronucleimentioning
confidence: 99%
See 1 more Smart Citation
“…In the Paramecium aurelia species complex, Pasternak [1967] reported that a small amount of RNA was synthesized in the micronucleus. In P. caudatum, there is no evidence of transcriptional activity during conjugation, although RNA synthesis in micronuclear S was reported [Rao and Prescott, 1967]. Nevertheless, there is strong evidence of micronuclear functioning during conjugation.…”
Section: Introductionmentioning
confidence: 94%
“…Like most ciliates, O. trifallax contains two types of nuclei: a somatic macronucleus (MAC) and a germline micronucleus (MIC). The MIC participates in sexual conjugation, but is otherwise transcriptionally silent (Narasimharao and Prescott 1967). During conjugation, O. trifallax destroys approximately 95% of its MIC genome and reorganizes the remaining pieces to generate over 20,000 highly processed MAC chromosomes, or nanochromosomes, typically bearing only a single gene (Prescott 2000; Swanton et al 1980).…”
Section: Introductionmentioning
confidence: 99%